KETERKAITAN SEKTOR DAN SEKTOR UTAMA DALAM PEREKONOMIAN PROPINSI BENGKULU: ANALISA INPUT- OUTPUT - Ketut Sukiyono; M. Mustopa Romdhon; Musriyadi Nabiu (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
The objective of research was to evaluate backward (BL) and forward linkages (FL) and to determine key sectors which have large contribution to Bengkulu economy. The linkages and key sector analyses were applied to the Bengkulu Input-Output Tables 2000. The results showed that the structure of the Bengkulu economy still remain dominated by agricultural sectors. Three agricultural sectors, i.e, palm oil, other agriculture, husbandary and their products, were the key sectors in Bengkulu economy indicated by strongest BL and FL indexes and they would be fundamental sectors for economic development in Bengkulu.